Biosafety and biological factors - Szopa, Monika; Leśków, Anna; Tarnowska, Małgorzata; Sarnowska, Marta; Wysocki, Andrzej; Pieńkowski, Marek; Wrzesiński, Janusz Adam (Journal of Education, Health and Sport, 2018)
Biological threats go beyond infectious disease epidemics. A biological threat should be construed as the effects of deployment of biological warfare or the occurrence of biological events of natural origin, which can have significant impact on the breach of security in the military, social, ecological and biological context. Biological factors are often recognized as an important and increasingly appreciated problem of widely understood public health. Epidemiological data indicates that, worldwide, at least several hundred million people are exposed to them. A fallacious conviction prevails that biological factors generally affect health care workers who are exposed to them as part of their daily professional routine. However, we rarely realize that biological factors affect us as part of many types of work, also in public spaces. Exposure to biological factors in the workplace and out of work has become increasingly frequent, leading to many adverse health effects. Health care authorities should be sensitive to the emergence of disease foci caused by biological factors (bioterrorism), which requires their quick reaction. It is also important to guarantee the security of personnel in all employment areas where contact with these factors is expected. It is estimated that the frequency of use of weapons of mass destruction is directly proportional to the availability of these means and their production costs, as well as their production capacity. These are the main reasons that indicate that a growing number of terrorist organizations can start using them. The purpose of the study is to present the current knowledge on the preparedness of government bodies (administration and health care) to fight biological threats of various origin.